A história do ensino de física no Brasil n o século XIX: as academias militares e o colégio Pedro II - Beneti, Alysson Cristiano [UNESP] (2014)
The objective of this study is to set a historical notation on the teaching of Physics in Brazil focusing three teaching institutions. The research problem is expressed by the subject: which were the characteristics of the teaching of Physics in the Real Academia de Artilharia, Fortificação e Desenho (from 1792 to 1810), Academia Real Militar (from 1810 to 1822) and in Colégio Pedro II (from 1838 to 1839)? The goal of the historical documents analysis is confronted with historical narratives of secondary sources. The theoretical referencial used is it of the historiography supported in a tool of textual speech by Teaun Adrianus Van Dijk. It is a qualitative and descriptive research. We observed through the analysis of the data that in Real Academia de Artilharia, Fortificações e Desenho between the years of 1792 and 1810, physics teaching was accomplished with theoretical classes complemented with field practical classes, aiming the understanding of the production and handling of warlike workmanships, as well as planning and building site. In the Academia Real Militar, between 1810 and 1822, Physics was a specific discipline, apart from other disciplines, what highlighted its larger importance in the grating of contents. The teaching itself was for theoretical exhibition. The goal of physics teaching was forming professionals for the work of military defense and building site. The Physics books used presented detailed and diversified contents. In Colégio Pedro II physics teaching was for exhibition, without concern about mathematics in a first period and the teaching for encyclopedia, for exhibition and conceptual with concerning mathematics of physical problems and with activities of experimental practices in laboratories of a second period. We obsserved that pedagogical practices used at nowadays schools are taken root culturally and historically in old practices of physics teaching, as well as the present contents belonging to...